Radiofrequency ablation-induced superior vena cava stenosis in a 5-year-old boy with congenital left atrial appendage deformity: a case report and literature review - Xiong, Jianxian; Wenbo, Yu; Gao, Jianfeng; Li, Meifang; Yu, Dongmin (Frontiers in Surgery, 2023)
Superior vena cava (SVC) stenosis is rarely caused by iatrogenic trauma. Herein, the case of a 5-year-old boy who underwent radiofrequency ablation for paroxysmal supraventricular tachycardia but developed SVC stenosis and related syndromes is reported. Notably, the child exhibited an enlarged left atrial appendage that had partially breached the pericardium. Subsequent interventions involved successful removal of the stenosis, artificial vascular reconstruction, and comprehensive radiofrequency ablation of the entire right atrium, along with ligation of the left atrial appendage under direct vision. As a result, the child experienced relief from symptoms.